Evaluating the Bibit App: The HEART Framework Approach in UX Design - Setya Perdana, Dandi; Lintang Yuniar Banowosari (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
With the rise of investment applications like Bibit in Indonesia, evaluating user experience is crucial to improve user engagement and satisfaction. This study aims to assess the user experience of the Bibit app using the HEART framework to identify areas for improvement. A descriptive survey was conducted using the Slovin method to determine a sample size of approximately 100 people. The study used a questionnaire distributed through Google Forms that measures the five aspects of the HEART framework on a Likert scale. Data were analyzed for validity and reliability using IBM SPSS and stored in Google Spreadsheets. In general, the Bibit app demonstrated high satisfaction, engagement, adoption, retention, and task success among its users, with most categories scoring above the 80% target. However, specific areas, particularly Happiness 2, Adoption 1, Retention 1, and Task Success 3, require further development attention. The Bibit app provides a generally satisfying user experience, with significant potential for improvement in navigation tooltips, investment product development, and app speed and efficiency.